The effect of 10% pegagan (centella asiatica (L.) urban) extract cream on melanin amount in the guinea pig skin vitiligo model - Harahap, Marina (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Pegagan is one of the plants used by the community for medicinal purposes; it contains a variety of compounds, including the following: Pegagan contains antioxidant and anti-inflammatory effects. The in vivo effects of repigmenting chemicals generated from centella asiatica extract have not been explored prior to this study. The objective is to demonstrate that 10% pegagan extract cream affects melanin levels in guinea pig models of vitiligo. Subjects and Methods This is a strictly experimental study with a post-test-only control group design involving the administration of 10% centella asiatica extract cream. In this study, 16 male guinea pigs were divided into two groups. Both groups of guinea pigs had cream containing hydroquinone administered to their backs daily for eight days. The control group then did not get any treatment. The treatment group received a 10% Pegagan extract lotion for fourteen days. Histopathological examination of tissue stained with Masson-Fontaine. The amount of melanin is based on the ratio of pixels in the melanin area to the total number of pixels in the epidermal tissue. Results The group that got 10% Pegagan extract cream had the highest concentration of melanin, and the difference was statistically significant (p0.05). Conclusion The conclusion of this study is that 10% centella asiatica extract cream improves the level of melanin in the skin of guinea pigs with a vitiligo model. Keywords: centella extract, melanin, and hydroquinone